Active Starch-Polyester Bilayer Films with Surface-Incorporated Ferulic Acid - Eva Hernández-García; Maria Vargas; Amparo Chiralt (Membranes, 2022)
Bilayer films of cassava starch-based (with 10% gellan gum) and polylactic (PLA): Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) polyester blend (with 75% PLA) monolayers were obtained by melt-blending and compression-molding, and the subsequent thermocompressing of both monolayers. Ferulic acid (FA) was incorporated into the polyester sheet by spraying and drying. Films were characterized in terms of their microstructure and functional properties throughout two months of storage at 25 °C and 53% relative humidity. The laminates exhibited improved tensile and barrier properties compared to the respective monolayers, which makes them more adequate for food packaging purposes. Surface incorporation of ferulic acid did not significantly modify the barrier and mechanical properties of the films while providing them with antioxidant and antibacterial capacity when applied in aqueous systems, where a complete release of active compounds occurred. The physical properties of the bilayers and layer thermo-sealing were stable throughout storage. Likewise, the antioxidant and antimicrobial active properties were preserved throughout storage. Therefore, these active bilayers represent a sustainable packaging alternative to non-biodegradable, non-recyclable synthetic laminates for food packaging purposes, which could extend the shelf-life of food due to their antioxidant and antibacterial properties.